A Comparative Study on the Paradoxical Relationship Between Heavy Metal Exposure and Kidney Function - Jee Hyun Rho; Seungho Lee; Jung-Yeon Kwon; Young-Seoub Hong (Diagnostics)
Introduction: Korea has higher levels of heavy metals compared to other countries, raising the need to study the health impacts on vulnerable populations. This study examined the effects of heavy metal exposure—lead, mercury, and cadmium—on kidney function in residents of environmentally vulnerable areas compared to the general population in Korea. Methods: Epidemiological studies in vulnerable areas and official data from the Fourth Korean National Environmental Health Survey were analyzed to assess blood levels of lead and mercury and urinary cadmium. An integrated heavy metal concentration was calculated, combining the levels of these metals. Kidney function was evaluated using the estimated glomerular filtration rate (eGFR), classified into normal, mildly reduced, and impaired. Correlation and logistic regression analyses were used to examine relationships between heavy metal levels and eGFR. Results: The integrated heavy metal concentration in vulnerable areas was higher than in the general population. In the general population, increased heavy metal levels were associated with a decrease in eGFR, whereas in vulnerable areas, eGFR increased with higher heavy metal levels. In the general population, a rise in urinary cadmium increased the risk of eGFR decline by 19.9%, while in vulnerable areas, higher urinary cadmium reduced this risk by 23.3%. Conclusions: Contrasting relationships between heavy metal exposure and eGFR in vulnerable areas versus the general population may be due to long-term exposure and reduced renal excretion. This study underscores the need for continued monitoring in vulnerable areas, and future research should identify eGFR thresholds that correlate with heavy metal level shifts.